Rural teaching practice. A didactic improvement program in Yurimaguas - Guzmán Valles, Hugo (2022)
Teaching practice in rural areas has constituted a pedagogical challenge in recent years, however, it has revealed problems related to the commitment and identity of teachers in innovating their educational practice. The objective of the study was to design a Didactics in Action program to improve rural teaching practice in Yurimaguas, 2021. A qualitative investigation was carried out and the participation of primary level teachers could be counted on, who were interviewed without any inconvenience. The results showed that there is teacher indifference to updating, which implied the urgent need to formulate improvement proposals that addressed the identified problem. It was concluded that rural teaching practice is in a process of change that involves theoretical, methodological, digital, and investigative aspects that will serve as support in the development of students' learning.